Need assessment of spiritual care in health services: The experts’ views - Farzaneh Maftoon; Mojgan Sharifan; Fatemeh Naghizadeh Moghari; Mahmoud Tavoussi (Payesh, 2020)
Objective (s): Patients suffering from different illnesses might need spiritual care especially those who are suffering from chronic diseases. The aim of this study was to perform a need assessment study of spiritual care. Methods: This was a qualitative study. First a questionnaire was designed based on literature review and experts opinions. Then this questionnaire was administered to a panel of experts using the Delphi method. The panel were experts in psychiatry, social medicine, epidemiology, quality of life, medical ethics, pediatric, nursing, occupational medicine and religion. Results: Experts indicated that patients with chronic diseases, patients with acute diseases at recovering period, incurable diseases, the patients at the end of life and also their families have priority for receiving spiritual care. Moreover they indicated that those with addiction, psychiatric diseases, sexual problems, HIV positive and infertility problems need spiritual care. Conclusion: Spiritual care could be integrated into the mainstream medical treatment. However, patients’ medical condition, culture, medical ethics and patient choice have important role in delivery of spiritual care.